Does sex mediate the affective response to high intensity interval exercise? - Astorino, T. A.; Sheard, A. C. (Physiology & Behavior, 2019)
• Affect is positive at low to moderate exercise intensities yet is more aversive at intensities above the lactate threshold. • Women and men differ in regards to muscle fiber type and muscle mass. • This study examined if sex alters the affective response to interval based exercise. • Data show lower affective valence and higher blood lactate concentration in men versus women. • Clinicians may need to consider sex of their clientele when prescribing interval based exercise.